Sitravatinib combined with venetoclax exerts effective synergy to eliminate acute myeloid leukemia cells with FLT3-ITD mutations - Jie Yang; Yvyin Zhang; Qingshan Li; Peihong Wang (Translational Oncology)
We have previously identified sitravatinib as a potent inhibitor of FLT3, capable of overcoming resistance to gilteritinib in the treatment of acute myeloid leukemia (AML). The combination of venetoclax and FLT3 inhibitors gilteritinib and quizartinib has shown promising results in reducing leukemia burden and improving survival in pre-clinical studies and clinical trials of AML with FLT3 mutation. In this study, we aimed to investigate the therapeutic effect of treating AML with sitravatinib combined with venetoclax. Our findings indicated that the combination of sitravatinib and venetoclax significantly decreased cell viability and increased cell apoptosis in AML cell lines harboring FLT3 mutation, more so than either treatment alone. These two agents exerted strong synergistic effects in FLT3-ITD AML cell lines and patient bone marrow cells in vitro. The activation of MAPK/ERK signaling are common causes that weaken the efficacy of FLT3 inhibitors, while the upregulation of anti-apoptotic proteins including BCL-xL and MCL-1 leads to venetoclax resistance. Our data demonstrated that sitravatinib plus venetoclax further suppressed the phosphorylation of AKT and ERK as well as downregulated MCL-1 and BCL-xL, which mechanically explain the synergistic effect. Finally, we tested the potential application of sitravatinib plus venetoclax in vivo using patient-derived xenografts, and found that the combined therapy was significantly more effective in inhibiting leukemia cell expansion, reducing infiltration in the spleen, and prolonging survival time compared to a single administration. Our study demonstrates the potential use of sitravatinib plus venetoclax as an alternative therapeutic strategy to treat AML patients with FLT3-ITD mutation.